Ambulanz für Geflüchtete mit Traumafolgestörungen und psychischen Belastungen in einer Landeserstaufnahmeeinrichtung - Manok, Natalie; Huhn, Daniel; Kohl, Rupert Maria; Ludwig, Max; Schweitzer, Jochen; Kaufmann, Claudia; Terhoeven, Valentin; Ditzen, Beate; Herpertz, Sabine; Herzog, Wolfgang; Nikendei, Christoph (Psychotherapeut, 2017)
In 2015 over 400,000 asylum applications were lodged in Germany in the wake of the global refugee movement. War, torture, traumatic experiences during migration and postmigration stressors all lead to considerable psychological burdens in refugees. To ensure the provision of psychosocial care to refugees in the Heidelberg-Kirchheim reception center in the state of Baden-Wuerttemberg, a psychosocial outpatient clinic was established in February 2015. This article presents the objectives of the psychosocial outpatient clinic as well as the implementation process. Furthermore, it examines the spectrum of patient disorders and perspectives of practitioners with respect to beneficial effects as well as difficulties arising and limitations of treatment within the context of a refugee reception facility. Over the course of 10 months 317 patients sought treatment in the clinic. Posttraumatic, depressive and anxiety disorders as well as addictive disorders were the most common clinical diagnoses. Most of the practitioners saw challenges in the multitude of severe and at times burdening patient fates, the large number of patients, the provision of adequate interpreter services and the restricted planability of patient contacts. By providing treatment to the severely burdened refugees, the clinic endeavors to meet the high demand for psychosocial care. Following the initial implementation phase, there are important further developments to be made, which are discussed in this article.